Longitudinal change in cardiac structure and function following acute coronary syndrome stratified by culprit coronary artery lesion site. (8th February 2021) - Ravnkilde, K; Skaarup, K; Grove, GL; Modin, D; Nielsen, AB; Falsing, MM; Iversen, AZ; Pedersen, S; Fritz-Hansen, T; Galatius, S; Jespersen, T; Shah, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Acute coronary syndrome (ACS) has adverse consequences for the myocardium and subsequent cardiac function and structure. No reports exist comparing the differences in impact of culprit coronary artery lesion site on longitudinal remodeling and changes left ventricular structure and function. Method: A total of 299 ACS patients treated with PCI were included in the present study. All patients had two echocardiographic examinations performed. The first was performed median 2 (IQR: 1; 3) days following PCI, while the second was performed median 240 (IQR: 81; 881) days after the first. Patients were grouped based on culprit coronary artery lesion (left anterior descending artery (LAD), right coronary artery (RCA) and circumflex artery (Cx)). Patients with multiple lesions were excluded from the present study. Univariable linear regression analysis was utilised to assess the association between culprit coronary artery lesion site and longitudinal change in cardiac structure and function. Results: Mean age was 63 ± 11 years and 77% were male. At follow-up, mean left ventricular ejection fraction was 42 ± 9% and global longitudinal strain (GLS) was -13 ± 4%. Culprit coronary artery lesion was allocated as follows; 168 ACS patients were treated in LAD, 95 patients were treated in RCA, and 36 patients were treated in Cx. In the linear regression analysis, LAD patients displayed a greater improvement in GLS (b =-0.116, p = 0.048) compared to the two other lesion sites. LAD patients had the poorest GLS at both baseline and follow-up echocardiography (Figure). RCA lesions were associated with the largest decrease in left atrial maximum volume (LAVmax) (b = -0.156, p = 0.011) and the largest increase in relative wall thickness (RWT) (b = 0.139, p = 0.030), consequently resulting in an LAVmax smaller and an RWT larger at follow-up than other lesion sites (Figure). Lastly, Cx lesions were significantly associated with the largest decrease in ratio between peak early diastolic transmitral flow velocity and peak early diastolic mitral annular tissue velocity (E/e') (b = -0.262, P <0.001). Cx lesion patients were observed to have elevated E/e' at baseline, which generally normalised at follow-up (Figure). Conclusion: The present study suggests that culprit coronary artery lesion site has a differential impact on cardiac remodeling. This information can potentially aid the clinical understanding of cardiac structure and function following ACS according to coronary artery lesion site.